Pelatihan Pengelolaan Aset Desa Bagi Perangkat Desa Ciburial Dan Mandala Mekar - Khairul Shaleh; Saadah Saadah (STMIK Royal, 2023)
Abstract: The gap between the role of treasurer and financial affairs with competence becomes an obstacle in the accountability process for using village finance. Increasing the capacity of village officials in the village financial management and administration is the goal of implementing community service programs in the village government of Ciburial, Mandala Mekar, and Mekarsaluyu Kab. Bandung, West Java Province. The treasurer and village finance department will be provided with assistance on village financial administration and management. The implementation of this program uses the mentoring method for the treasurer and the village finance department in each community service partner. This activity will provide a conceptual and technical understanding of the administration and management of village assets. Furthermore, the treasurers and the finance department will be asked to simulate the preparation of the accountability report. To provide better results in implementing this program, we, together with the team, will provide assistance and training related to managing and administering village assets. This activity program will make it easier for asset managers to prepare village accountability reports following applicable regulations. Keywords: mentoring; village assets; village government Abstrak: Kesenjangan antara peran sebagai bendahara dan urusan keuangan dengan kompetensi menjadi kendala dalam proses pertanggungjawaban penggunaan keuangan desa. Peningkatan kapasitas perangkat desa dalam bidang pengelolaan dan penatausahaan keuangan desa merupakan tujuan dalam pelaksanaan program pengabdian kepada masyarakat di pemerintah desa Ciburial, Mandala Mekar dan Mekarsaluyu Kab. Bandung Propinsi Jawa Barat. Bendahara dan Bagian keuangan desa yang akan diberikan pendampingan tentang penatausahaan dan pengelolaan keuangan desa. Pelaksanaan program ini dengan menggunakan metode pendampingan bagi bendahara dan bagian keuangan desa di masing masing mitra pengabdian masyarakat. Kegiatan ini akan memberikan pemahaman konsep dan teknis tentang penatausahaan dan pengelolaan aset desa. Selanjutnya para bendahara dan bagian keuangan akan diminta untuk menjalankan simulasi penyusunan laporan pertanggungjawaban. Untuk memberikan hasil yang lebih baik dalam pelaksanaan program ini kami bersama dengan tim akan memberikan pendampingan dan pelatihan berkaitan dengan pengelolaan dan penatausahaan aset desa. Program kegiatan ini akan lebih memudahkan bagi pengelola aset menyusun laporan pertanggungjawaban desa sesuai dengan aturan berlaku.Kata kunci : aset desa; pemerintah desa; pendampingan.